Trade Agreements and Agribusiness Export Performance: Ppml Gravity Evidence from Indonesian Palm Oil Hs 1511 (2015–2023) - Tuegeh, Octavia Diana Monica; Paat, Franda Benedicta; Tumiwa, Johan R. (Sam Ratulangi University, 2026)
This study examines Indonesia’s export performance in an agribusiness product at the HS 6-digit level (HS 1511) over 2015-2023 by combining revealed competitiveness indicators and structural gravity estimation. First, we compute the Revealed Comparative Advantage (RCA) index to assess Indonesia’s export specialization relative to world trade. Second, we estimate a Poisson pseudo-maximum likelihood (PPML) gravity model with year fixed effects to identify the roles of destination market size, trade costs, and trade agreement coverage. Bilateral exports are constructed from UN Comtrade, macroeconomic controls are drawn from the World Development Indicators, bilateral distance and dyadic controls are obtained from CEPII, and trade agreement status is coded from DESTA at the dyad–year level using an in-force rule. Results indicate that Indonesia retains a strong revealed comparative advantage (RCA > 1 in all years), although the average RCA declines between early and late sub-periods. Gravity estimates show that destination market size (particularly population) positively predicts exports, while distance reduces expected export values. Importantly, in-force regional trade agreements are associated with significantly higher bilateral exports, approximately 48% larger export values, ceteris paribus, highlighting the relevance of policy-enabled market access alongside traditional gravity fundamentals. These findings emphasize the joint importance of competitiveness, trade-cost reduction, and effective utilization of trade agreements for sustaining and expanding Indonesia’s agribusiness exports. Keywords: comparative advantage, gravity model, Indonesia, PPML, trade agreements